Aster tataricus L. f.: a review on the botany, phytochemistry, ethnopharmacology, pharmacology, toxicology and comprehensive utilization - Zhang, Xinyi; Liu, Meiqi; Zhang, Xiaozhuang; Ma, Lengleng; Song, Shiyi; Pan, Meitong; Huang, Shumin; Ren, Weichao; Ma, Wei (Frontiers in Pharmacology, 2025)
Aster tataricus L.f. (A.tataricus), a perennial herb of the genus Aster in the Asteraceae (Compositae) family. It is associated with a spicy, bitter, and warm nature and belongs to the Lung Meridian. The medicinal parts of A.tataricus are flowers, leaves, roots, and rhizomes. A.tataricus was first recorded in Shuo Wen under the alias “Zi Wan” (茈菀). Traditionally, it is utilised to clear lung qi, promote fluid flow, calm adverse-rising energy, relieve cough, resolve sputum, and regulate secretions. However, it is worth noting that A.tataricus has certain hepatotoxicity. Modern pharmacology indicates that A.tataricus can be used to treat various diseases, including those of the respiratory and urinary systems. In this review, all available information on A.tataricus was collected via academic databases such as PubMed, SciFinder Scholar, CNKI, iPlant, Google Scholar, Web of Science, GBIF, and Masterpieces of Traditional Chinese Medicine. To date, more than 200 metabolites have been isolated and characterized from A.tataricus, including terpenoids, flavonoids, polypeptides, and others. These compounds demonstrate a wide range of pharmacological activities, such as anti-inflammatory effects, antitussive and bronchodilatory properties, anticancer activity, antioxidant effects, treatment of osteolytic disorders, management of urinary system diseases, alleviation of acute lung injury, and enhancement of memory. Meanwhile, the different polarity extracts of A.tataricus also exhibit some toxicological characteristics, the astin has a similar structure to that of cyclochloridine, the hepatotoxic metabolite of penicillin; its saponins also have hemolytic effects. However, there are currently few studies on the toxicology of A.tataricus. Further in-depth research is needed to explore the potential mechanisms underlying the toxicity of A.tataricus. The toxicity of A.tataricus can be reduced through compatibility and processing, but this aspect has received little discussion and further research on quality standardization is needed. To ensure the sustainable development of A.tataricus, we have also summarized its artificial cultivation techniques. Shionone and astin are the characteristic components of A.tataricus. Their pharmacological effects have been deeply studied, but the research on other metabolites is relatively scarce. Therefore, this article focuses on botany, artificial cultivation, phytochemistry, ethnopharmacology, pharmacology, toxicology, and comprehensive utilization of A.tataricus. Discuss the future research prospects and existing problems of A.tataricus, and provide references for further research on A.tataricus and the establishment of quality control standards.